Weak laws of large numbers for arrays of rowwise negatively dependent random variables. (2001) - Taylor, R. L.; Patterson, R. F.; Bozorgnia, A.
Abstract : Weak laws of large numbers for arrays of rowwise negatively dependent random variables are obtained in this paper. The more general hypothesis of negative dependence relaxes the usual assumption of independence. The moment conditions are similar to previous results, and the stochastic bounded condition also provides a generalization of the usual distributional assumptions.